Jämförelse mellan renskötsel och betesbaserad fårskötsel - Bäckström, Julia (2011)
This essay describes and compares the extensive reindeer management to the more intensive, but grazing based, sheep management system in Sweden. Differences and similarities between the two production systems will be investigated by elucidating the economy, land use and possibilities to influence production and economy through breeding, feeding and product development. The reindeer management area covers the northern part of Sweden whilst the sheep management is dispersed over the country. Both reindeer and sheep are ruminants and have relatively high demands on the quality and digestibility of the feed however reindeers graze on mountain-and forest lands whilst sheep often graze inaccessible areas or cultivated grasslands. Selection intensity is generally lower in the reindeer management compared to the intensity in sheep breeding. The size of the annual income for a reindeer owner with 400 reindeer is calculated to approximately 100 000 SEK. The annual income for a sheep farmer with 400 animals can vary between 80 000 and 200 00 SEK. In both cases the income is based on the sale of meat and other products from the animals, but also from allowances. The conclusion is that reindeer- and sheep management in Sweden differs in many ways despite the animals not being much different from each other. The sheep management is often small-scale whereas the reindeer management usually is large-scale. The way the animals are kept differs since in most cases there is only one person owning the sheep and the land they are kept on. In reindeer management the companies have several owners, each having a different amount of reindeers, not owning the land themselves.